Lexical Ambiguity in the “The Merry Adventures of Robin Hood” Novel by Howard Pyle - Arief Hadziq Fikri; Rio Rizky Octora (Channing : Journal of English Language Education and Literature, 2023)
This study aims to find the types and amount of Lexical Ambiguity in the novel "The Merry Adventures of Robin Hood" by Howard Pyle. The method used in this research is the descriptive qualitative method. The data collection technique used in this study has several steps, namely understanding lexical ambiguity, reading the novel, finding out lexical ambiguity words in the novel, and making a note of the lexical ambiguity words of the novel. The data source for this research is the novel "The Merry Adventures of Robin Hood" by Howard Pyle. The focus of the research is homonyms, homographs, and homophones. Based on the results of data analysis the use of the word lexical ambiguity as much as 73 data. The first number of findings, the use of homonyms was 19 findings (26%). This word is two or more words that have the same pronunciation but different meanings. Second, Homographs with a total of 30 findings (41%). This word has the same spelling, but its pronunciation and meaning are different. and the Third, Homophone with a total of 24 findings (33%). These words are spelled differently but have a similar pronunciation. Thus, from this amount, it can be concluded that the novel The Merry Adventures of Robin Hood by Howard Pyle found many uses of the word lexical ambiguity with a total of 73 data findings, and the most domineering use of the word is found in the use of Homographs with 30 data findings with a percentage of 41 %.